WEBSITE REGULATORY LAWS OF THE USA - Filinovych, Valeriya V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the provisions and features of US law in relation to the regulation of websites and to suggest provisions useful for incorporation into Ukrainian legislation in the field of Internet regulation. The methodological basis of the research comprises philosophical, ideological, general scientific and special methods. Results: the American legislation in the field of regulation of copyright protection relations in general on the Internet and on websites in particular was shown as one of the most successful. Also the author found out that there a lot of blanks as to this issue in Ukrainian legislation. The author suggested for the lawmaker of our state to adopt the experience of American colleagues in regulating the legal relations related to electronic resources. Discussion: improvement of the national legislation in the sphere of Internet regulation on the example of acts of the USA; search for actions to be taken while dealing with the website regulation.